Dose-response relationship between epidural bupivacaine dose and mortality risk after surgical resection of nonsmall-cell lung cancer. Issue 9 (23rd September 2022) - Wu, Hsiang-Ling; Tai, Ying-Hsuan; Li, Chun-Cheng; Cata, Juan P.; Wang, Chien-Wun; Chang, Kuang-Yi; Tsou, Mei-Yung; Lin, Shih-Pin
Abstract : Background: Preclinical studies have shown that local anesthetics may modify the growth and invasion of cancer cells. However, few clinical studies have evaluated their impact on cancer outcomes after tumor resection. Methods: In this single-center cohort study, patients who underwent surgical resection of stage IA through IIIB nonsmall-cell lung cancer and used patient-controlled epidural analgesia from 2005 to 2015 were recruited and followed until May 2017. Data of the epidural bupivacaine dose for each patient were obtained from infusion pump machines. Proportional hazards regression models were used to analyze the associations between bupivacaine dose with postoperative cancer recurrence and all-cause mortality. Results: A total of 464 patients were analyzed. Among these patients, the mean bupivacaine dose was 352 mg (± standard deviation 74 mg). After adjusting for important clinical and pathological covariates, a significant dose-response relationship was observed between epidural bupivacaine dose and all-cause mortality (adjusted hazard ratio: 1.008, 95% confidence interval: 1.001–1.016, p = 0.029). The association between bupivacaine dose and cancer recurrence were not significant (adjusted hazard ratio: 1.000, 95% confidence interval: 0.997–1.002, p = 0.771). Age, sex, body mass index, mean daily maximum pain score, and pathological perineural infiltration were independently associated with bupivacaine dose. Conclusion: A dose-dependent association was found between epidural bupivacaine dose and long-term mortality among patients following surgical resection of nonsmall-cell lung cancer. Our findings do not support the hypothetical anticancer benefits of local anesthetics. More studies are needed to elucidate the role of local anesthetics in cancer treatment.